Disease burden and conditioning regimens in ASCT1221, a randomized phase II trial in children with juvenile myelomonocytic leukemia: A Children's Oncology Group study. Issue 7 (12th March 2018) - Dvorak, Christopher C.; Satwani, Prakash; Stieglitz, Elliot; Cairo, Mitchell S.; Dang, Ha; Pei, Qinglin; Gao, Yun; Wall, Donna; Mazor, Tali; Olshen, Adam B.; Parker, Joel S.; Kahwash, Samir; et al.
Abstract: Background: Most patients with juvenile myelomonocytic leukemia (JMML) are curable only with allogeneic hematopoietic cell transplantation (HCT). However, the current standard conditioning regimen, busulfan‐cyclophosphamide‐melphalan (Bu‐Cy‐Mel), may be associated with higher risks of morbidity and mortality. ASCT1221 was designed to test whether the potentially less‐toxic myeloablative conditioning regimen containing busulfan‐fludarabine (Bu‐Flu) would be associated with equivalent outcomes. Procedure: Twenty‐seven patients were enrolled on ASCT1221 from 2013 to 2015. Pre‐ and post‐HCT (starting Day +30) mutant allele burden was measured in all and pre‐HCT therapy was administered according to physician discretion. Results: Fifteen patients were randomized (six to Bu‐Cy‐Mel and nine to Bu‐Flu) after meeting diagnostic criteria for JMML. Pre‐HCT low‐dose chemotherapy did not appear to reduce pre‐HCT disease burden. Two patients, however, received aggressive chemotherapy pre‐HCT and achieved low disease‐burden state; both are long‐term survivors. All four patients with detectable mutant allele burden at Day +30 post‐HCT eventually progressed compared to two of nine patients with unmeasurable allele burden ( P  = 0.04). The 18‐month event‐free survival of the entire cohort was 47% (95% CI, 21–69%), and was 83% (95% CI, 27–97%) and 22% (95% CI, 03–51%) for Bu‐Cy‐Mel and Bu‐Flu, respectively ( P  = 0.04). ASCT1221 was terminated early due to concerns that the Bu‐Flu arm had inferior outcomes. Conclusions: The regimen of Bu‐Flu is inadequate to provide disease control in patients with JMML who present to HCT with large burdens of disease. Advances in molecular testing may allow better characterization of biologic risk, pre‐HCT responses to chemotherapy, and post‐HCT management.